Microscopic Characteristics of Fault Gouge in Minor-Surface-Rupture Faults: A Case Study in the Longmenshan Fault Zone, Eastern Tibetan - Li, Yanbao; Chen, Lichun; Ran, Yongkang; Chang, Yuqiao (Frontiers in Earth Science, 2022)
Active faults with potential earthquake magnitude of 6–7 are often incorrectly identified as non-Holocene active faults by traditional geological methods because their co-seismic displacements were very small or even did not reach to surface, and are defined as minor-surface-rupture faults. Geological studies associated with the 2013 Lushan Ms 7.0 earthquake show that the Dachuan–Shuangshi fault (DSF) in the southern segment of the Longmenshan fault zone (LFZ) is a minor-surface-rupture fault. This study focuses on the microstructure and mineral composition of the fault gouge in the DSF using optical microscopy, a scanning electron microscope (SEM), and X-ray diffraction (XRD) methods; then, we compare our results with the previous achievements in the Beichuan–Yingxiu fault (BYF), a major seismogenic fault of the 2008 Wenchuan earthquake, in the middle–northern segment of the LFZ. The results show that the microscopic characteristics of the fault gouge of the DSF are obviously different from those of the BYF in the following aspects: 1) the thickness of the fault gouge produced by one fault event is less than 5 mm; 2) under the microscope, no obvious micro-cracks were examined in surrounding rocks around the fault gouge, and discontinuous micro-cracks and untypical S-C fabrics in the fault gouge were observed; 3) under the SEM, reworked fragments were rare in the fault gouge; 4) the XRD mineral analysis reveals that the total clay content is less than 50%, the content of kaolinite is obviously higher than that of clinochlore, and the content of illite/smectite mixed layer is less than 30%. A contrastive analysis reveals the differences between the microscopic features of the fault gouge of the DSF and the BYF, which are systematical. Therefore, the abovementioned microscopic characteristics identified from the fault gouge in the DSF may be used as auxiliary indicators to identify minor-surface-rupture faults.